Preparation of antibodies to determine the association of mitoribosomal complexes with mitochondrial membrane - Zellner, Laura (Jihočeská univerzita, 2021)
The assembly pathways of mitoribosomes, descendants of bacterial ancestors producing proteins encoded by vestigial mitochondrial genomes, remains largely unknown. To shed light on structural features of a precursor of the highly divergent small mitoribosomal subunits (mtSSU) from Trypanosoma brucei, called mtSSU assemblosome, recently characterized by cryoEM, we raised antibodies against two assembly factors present in the complex and against two subunits of the mature mtSSU. We used the antibodies in pilot experiments to determine whether the assemblosome associates with the inner mitochondrial membrane.
Preparation of antibodies to determine the association of mitoribosomal complexes with mitochondrial membrane
Keywords: mitochondrial ribosome; mitoribosome; antibody production; trypanosoma brucei; recombinant protein; antigen; mitochondria; subcellular fractionation; mitochondrial ribosome; mitoribosome; antibody production; trypanosoma brucei; recombinant protein; antigen; mitochondria; subcellular fractionation